2022
DOI: 10.3389/fendo.2022.1037164
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics of various samples advancing biomarker discovery and pathogenesis elucidation for diabetic retinopathy

Abstract: Diabetic retinopathy (DR) is a universal microvascular complication of diabetes mellitus (DM), which is the main reason for global sight damage/loss in middle-aged and/or older people. Current clinical analyses, like hemoglobin A1c, possess some importance as prognostic indicators for DR severity, but no effective circulating biomarkers are used for DR in the clinic currently, and studies on the latent pathophysiology remain lacking. Recent developments in omics, especially metabolomics, continue to disclose n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 122 publications
1
9
0
Order By: Relevance
“…Several previous studies revealed the metabolite levels in vitreous or aqueous humor samples from patients with DR, which shared some altered metabolites with the current study [45]. For example, proline, glutamine, and citrulline were significantly increased in vitreous samples of PDR [46,47].…”
Section: Discussionsupporting
confidence: 83%
“…Several previous studies revealed the metabolite levels in vitreous or aqueous humor samples from patients with DR, which shared some altered metabolites with the current study [45]. For example, proline, glutamine, and citrulline were significantly increased in vitreous samples of PDR [46,47].…”
Section: Discussionsupporting
confidence: 83%
“…Excellent biomarkers should be specific and sensitive, be easily quantified in easy to take biological samples, and exhibit good linearity with the development of disease. Considering the complexity of the pathogenesis of DR, multiple biomarkers are seemingly more suitable than a single optimal one [18]. Regarding the metabolomics analysis, nuclear magnetic resonance (NMR) spectroscopy and mass spectrometry (MS) have both been developed.…”
Section: Discussionmentioning
confidence: 99%
“…MS is often used in tandem with liquid chromatography (LC) or gas chromatography (GC), which are techniques applied to separate metabolites, thereby improving the resolution of isobaric compounds. In addition, LC-MS has become widely used in recent years, as MS has better sensitivity than NMR, allowing a wider spectrum of metabolites to be measured [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[195]. In their study, Qi et al (2006) produced Ca-alginate microspheres containing bovine serum albumin (BSA) and subsequently incorporated them into a poly (L-lactic acid) (PLLA) W/O emulsion using electrospinning [196]. The inventors demonstrated a successful integration of BSA, while also achieving a sustained release that extended beyond the duration of the bare microspheres.…”
Section: Drug Deliverymentioning
confidence: 99%